Consumer interest in purchasing products made in-country vs. imported products & its relationship with consumer ethnocentrism - Kroll, Ryan Scott (My University, 2025)
With the rise of a global economy, instead of marketing to national consumers, companies sought to create international marketing plans as a way for consumers in other nations to experience a slice of life from their country of origin. With the click of a button, the demand for products such as Levi’s and Coca-Cola grew, and consumers now had the option to purchase international or domestic products. While some consumers openly accepted the variety of international products, others rejected them, sometimes with ethnocentric tendencies, finding it unpatriotic to support an international brand. To investigate the relationship between country of origin and ethnocentrism, an online survey was developed for thirteen countries, to capture consumers' interest and cost value on purchasing ten different food and beverage products. The purpose of this research is to investigate whether the relationship between country of origin and ethnocentrism exists with specific products or countries.
Keywords: Ethnocentrism; Consumer ethnocentrism; Country of origin; Food & beverage; GENE scale